Exciting Tales of Exotic Dark India: Aravind Adiga’s The White Tiger - Mendes, Ana Cristina (2010)
A revamped portrayal of a Dark India garnered an unparalleled visibility in 2008 with the award of the coveted Man Booker Prize for Fiction to Aravind Adiga’s debut novel The White Tiger.This article examines Adiga’s staging of a Dark India as a new-fangled object of exoticist discourses. It begins by considering The White Tiger as an ironic uncovering of the subsumption of a Dark India into the global literary marketplace at a time of a perceived shift in re-Orientalist representational practices and their western reception. Specifically, while taking the measure of the appraisal The White Tiger has received, this article questions the premises that underpin the most vehement critiques directed at the novel: on the one hand, that Adiga’s work offers a purportedly long-awaited creative departure from Salman Rushdie’s; on the other hand, that the characterization strategies followed by the novelist result in what critics have perceived as class ventriloquism and, accordingly, a re-Orientalized title character equipped with an “inauthentic” voice.